Examining the Physico-Chemical, Structural and Thermo-Mechanical Properties of Naturally Occurring Acacia Pennata Fibres Treated with kmno4 - Saavedra-Flores, E (Nature Research, 2023)
Natural fiber is a viable and possible option when looking for a material with high specific strength and high specific modulus that is lightweight, affordable, biodegradable, recyclable, and eco-friendly to reinforce polymer composites. There are many methods in which natural fibres can be incorporated into composite materials. The purpose of this research was to evaluate the physico-chemical, structural, thermal, and mechanical properties of Acacia pennata fibres (APFs). Scanning electron microscopy was used to determine the AP fibers diameter and surface shape. The crystallinity index (64.47%) was discovered by XRD. The irregular arrangement and rough surface are seen in SEM photos. The findings demonstrated that fiber has high levels of cellulose (55.4%), hemicellulose (13.3%), and low levels of lignin (17.75%), which were determined through chemical analysis and validated by Fourier Transform Infrared Spectroscopy (FTIR). By using FTIR, the functional groups of the isolated AP fibers were examined, and TG analysis was used to look into the thermal degrading behaviour of the fibers treated with potassium permanganate (KMnO4) Due to their low density (520 kg/m3) and high cellulose content (55.4%), they have excellent bonding qualities. Additionally, tensile tests were used for mechanical characterisation to assess their tensile strength (685 MPa) and elongation. © 2023, The Author(s).